Die heimliche Hauptstad
This broadcast focuses on the Bosnian city of Zenica during the war. Daily life in the besieged city is reflected on, showing destroyed buildings, the downtown market, and people waiting for food rations. The report highlights the ongoing problem of war profiteers stealing humanitarian aid and reselling it on the local market at prices few can afford. Refugees from surrounding villages are then shown giving testimonies to workers from the Zenica Documentation Center. The documentation center collects, records, and archives material evidence of war crimes in addition to the testimonies gathered, all in the hope that it will help build a case for an international tribunal. At the time of the report the ICTY had yet to be established. Ragib Hadzic, head of the Zenica Documentation Center, explains how the evidence is collected and the difficulties in working with the UN and other international organizations. Pictures and documents of accused perpetrators are shown with detail, including those of Veselin Nikolic. Prisoners are shown in the Zenica prison and some are interviewed.